Secuencia de enseñanza para la presentación del análisis del fenómeno de inducción electromagnética - Oyuela Mateus, Diana Isabel; Garzón Barragán, Isabel (Revista Científica, 2011)
In this paper develops a teaching sequence based on the teaching-learning approach by oriented research, to present the analysis of the phenomenon of electromagnetic induction in an introductory course on electromagnetism. This sequence is based on two premises: one is that “all knowledge is the answer to a question” and the other is that students construct their knowledge from their own experience, which is generated by the learning environments that foster teacher. In order that students achieve significant learning and macro explanations of the phenomenon of electromagnetic induction in the sequence are considered aspects such as education, the relationship of the emf induced magnetic flux variation in time through a circuit, the description of the phenomenon in terms of forces and the bond that exists between the induced emf and the measurements of current and voltage in a circuit. It should be noted that this article is part of a thesis being developed, for this implementation of the sequence is a task that will take place in the future.